2012
DOI: 10.1002/hep.25695
|View full text |Cite
|
Sign up to set email alerts
|

Androgen pathway stimulates MicroRNA-216a transcription to suppress the tumor suppressor in lung cancer-1 gene in early hepatocarcinogenesis

Abstract: Deregulation of microRNAs (miRNAs) is common in advanced human hepatocellular carcinoma (HCC); however, the ones involved in early carcinogenesis have not yet been investigated. By examining the expression of 22 HCC-related miRNAs between precancerous and cancerous liver tissues, we found miR-216a and miR-224 were significantly up-regulated, starting from the precancerous stage. Furthermore, the elevation of miR-216a was mainly identified in male patients. To study this gender difference, we demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 33 publications
6
81
0
Order By: Relevance
“…[30][31][32] Recent animal studies have shown that androgen increased HBV gene transcription, which was repressed by the estrogen pathway. [33][34][35] Serum testosterone level in chronic HBV-infected males was also associated with the severity of hepatocyte damage in our previous study. 36 The difference in HBeAg-negative hepatitis risk between genders is potentially linked to differences in risks of chronic liver insufficiency, liver cirrhosis, and hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…[30][31][32] Recent animal studies have shown that androgen increased HBV gene transcription, which was repressed by the estrogen pathway. [33][34][35] Serum testosterone level in chronic HBV-infected males was also associated with the severity of hepatocyte damage in our previous study. 36 The difference in HBeAg-negative hepatitis risk between genders is potentially linked to differences in risks of chronic liver insufficiency, liver cirrhosis, and hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 66%
“…seroconversion at [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][30][31][32][33][34][35][36][37][38][39][40], and >40 years of age, respectively. 5,6 These differences may be attributable to differences in the studied cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies that also analyzed control tissues, a higher AR expression was evident in tumoral tissues compared with peritumoral tissues, revealing that the disruption in AR homeostasis was associated with the incidence of HCC (15,18). Overexpression of AR in HCC cells may lead to the dysregulation of several molecules associated with cellular proliferation, tumor growth and/or metastasis (21,22,25). Findings from clinical HCC specimens revealed that an elevation in the levels of microRNA (miR)-216a and cell cycle-related kinase (CCRK) was positively correlated with an increase in the AR protein level, and that the overexpression of miR-216a and CCRK was associated with poor patient prognoses (18,25).…”
Section: Ar Alterations In Hccmentioning
confidence: 96%
“…Overexpression of AR in HCC cells may lead to the dysregulation of several molecules associated with cellular proliferation, tumor growth and/or metastasis (21,22,25). Findings from clinical HCC specimens revealed that an elevation in the levels of microRNA (miR)-216a and cell cycle-related kinase (CCRK) was positively correlated with an increase in the AR protein level, and that the overexpression of miR-216a and CCRK was associated with poor patient prognoses (18,25). By contrast, Ma et al (22) established that AR overexpression was only present in tumors with a size of <3 cm (22).…”
Section: Ar Alterations In Hccmentioning
confidence: 99%
See 1 more Smart Citation